Study on the takeoff landing number of emergency rescue aircraft demand after earthquake - xiuyan Zhang; hong Chi (MATEC Web of Conferences, 2019)
Due to the lack of information after earthquake, the demand for takeoff landing number of emergency rescue aircraft is not clear. The model for takeoff landing number of emergency rescue aircraft demand after earthquake is constructed. Firstly, the total task amount of emergency rescue is determined according to the number of injured persons and the number of victims after the earthquake. Then, according to the damage degree of the ground roads in the earthquake area, the amount of aviation emergency rescue mission is determined. Finally, based on the information of emergency rescue aircraft fleet, the actual takeoff landing number of emergency rescue aircraft is calculated. The rationality of the model is verified by the data of 5 actual earthquake events from 2008, to provide guidance for effective aviation emergency rescue after earthquake.